Investigation of Sugar Concentration and Lactobacillus acidophilus Inoculation on Pickled Turmeric Rhizome Production - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Curcuma longa which is the source of the spice turmeric having different phytochemical constituents, and pharmacological activities. An alternative way of preserving surplus turmeric rhizomes could be fermented to pickle products. Preservation of the turmeric rhizomes by fermentation can eliminate the undesired taste and improve flavor of this herb. Different technical parameters such as sugar addition (1.5%, 2.0%, 2.5%, 3.0%, 3.5%) and Lactobacillus acidophilus (0.1%, 0.2%, 0.3%, 0.4%, 0.5%) affecting to the pickling process were examined. Our results revealed that 3.0% sugar, 0.3% Lactobacillus acidophilus (1010 cfu/g) as starter culture were adequate for lactic fermentation. The consumption of pickled turmeric rhizomes helps enhance balanced human nutrition. Lactic acid fermentation retains all the natural plant ingredients while improving the quality, taste and aroma. The benefits of pickled turmeric have been better understood in terms of high content of valuable curcumin. It becomes an important phytochemical source for human health. Production of pickle from this herb can help increase added values and reduce post-harvest losses.Keywords: Turmeric rhizome, Lactobacillus acidophilus, Pickled, Fermentation, Starter culture, Sugar.